Pattern and Distribution of Injuries from the Fall from the Height in Fatal Cases in a Tertiary Care Hospital, Chennai - G. Amritha Sulthana; Yuhesh Somasundaram; Shankar Subramanian; Manoharan Chellasamy (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: The second leading cause for the injury related deaths is fall from height. The injuries fatalitiesdepends on the height of fall and its impact surface. Landing position is also considered as an important parameter.Aim: The aim of the study is to study the pattern and distribution of injuries from the fall from height in fatal cases.Methodology: This study includes 100 cases of victims brought to the tertiary care hospital with the history of fallfrom the height. The cases were brought from the accident site or after death as a consequence of fall in this tertiarycare hospital. During autopsy all the relevant details like basic details and the injury details like dimensions,injurytypes and the primary impact site were taken. Blood and urine examination were done for finding alcohol anddrugs. Data entered in MS excel and analysis done in SPSS 23 software. P value <0.05 is considered to be significant.Results: Majority of the study participants belongs to 31-40 years of age group(30%) followed by 41-50 years of age(18%). Male predominance was observed in our study (90%).34% were daily labours. The most common externalinjury is abrasion noted in 90% of the study participants. The most common primary impact site was head (50%)followed by backside (12%).Conclusion: Fall from heights cause significant morbidity and mortality. It is important to create awareness amongthe workers and to provide safety gears for the persons working in construction sites.